Pelatihan dan Sosialisasi Penggunaan Website Sekolah pada SD Muhammadiyah Tidore - Salkin Lutfi; Hairil Kurniadi Siradjuddin; Arifandi Mario Mamonto; Ardi Salman; Puput Purnamasari (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
This community service activity was carried out at Muhammadiyah Tidore Elementary School with a primary focus on improving the competency of teachers and staff in managing the school website. The background to this activity stems from the school's need for information media that is fast, accurate, and easily accessible to the community. The school website not only serves as a means of publishing activities but also as a communication medium between the school, parents, and the wider community. With good website management, information about academic activities, important announcements, and the school profile can be conveyed more effectively. The activity implementation method is carried out through several structured stages. The first stage is preparation, namely identifying needs, preparing training materials, and coordinating with the school. The second stage is technical training involving teachers and staff to understand the basics of content management, from adding articles, updating information, to uploading activity documentation. The third stage is socialization, where the community, especially parents, are introduced to the functions and benefits of the school website. Next, the implementation stage is carried out by directly applying the training results in website management. The final stage is evaluation, which aims to assess the extent to which skills improvements have been achieved and the extent to which the website is utilized by the community. The results of the activity indicate a significant increase in the skills of teachers and staff. They are able to independently update website content and utilize user guides provided in the form of documents and video tutorials. Furthermore, public access to online school information has also increased. This demonstrates that the school website is truly an effective communication tool. Therefore, this community service activity is expected to become a model for information technology empowerment that can be replicated in other schools, particularly in North Maluku.